The Effect Of Financial Literacy And Economic Literacy On The Financial Management Of Youth In Sumberejo Village - Anggraini, Ari Saputri Novita; Prastyaningtyas, Efa Wahyu; Irmayanti, Elis (Universitas Nusantara PGRI Kediri, 2024)
Research aim: This study investigates the potential influence of financial and economic literacy on the financial management of adolescents in Sumberejo Village. Design/Methode/Approach: A quantitative approach is employed, utilizing purposive sampling techniques for the selection of adolescent participants. Data analysis is conducted using t-tests, F-tests, and coefficient of determination testing with the assistance of SPSS software version 23. Research Finding: After analyzing the data, the study reveals a Fcount of 92,251, suggesting that there is a simultaneous impact of both financial and economic literacy on the financial management of adolescents residing in Sumberejo Village. Moreover, financial literacy and economic literacy account for a contribution of 0.569 and 56.9%, respectively, towards financial management.